2023
DOI: 10.3390/medicina59050843
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Prescribing Practices and Factors Related to Antibiotic Prescribing in Community Pharmacies

Abstract: Background and Objectives: Overprescribing of antibiotics is one of the important contributors of antimicrobial resistance globally. A high proportion of antibiotics prescribed in community settings are unnecessary or inappropriate. This study assesses the prescribing practices and factors related to antibiotic prescribing in community pharmacies in United Arab Emirates (UAE). Materials and Methods: A cross-sectional study utilizing a quantitative approach was carried out in the community pharmacies of Ras Al … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Even though the percentage of drugs prescribed from EMLs were lower compared to WHO optimal value for the current study, the results were higher than more other findings revealed from studies conducted in India (37.37%; 58.3%), Nepal (65.8%; 80.9%), UAE(47.7%; 83.8%), Sri Lanka (68.8%), and Sudan (81.19%) (Abu Farha et al, 2022 ; Aryal et al, 2020 ; Atal et al, 2021 ; Galappatthy et al, 2021b ; Mandal et al, 2022 ; Rabbani et al, 2023 ; Shrestha et al, 2021 ; Yousif & Supakankunti, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the percentage of drugs prescribed from EMLs were lower compared to WHO optimal value for the current study, the results were higher than more other findings revealed from studies conducted in India (37.37%; 58.3%), Nepal (65.8%; 80.9%), UAE(47.7%; 83.8%), Sri Lanka (68.8%), and Sudan (81.19%) (Abu Farha et al, 2022 ; Aryal et al, 2020 ; Atal et al, 2021 ; Galappatthy et al, 2021b ; Mandal et al, 2022 ; Rabbani et al, 2023 ; Shrestha et al, 2021 ; Yousif & Supakankunti, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings were higher than the WHO optimal value (100%). Comparing these results to others from previous similar studies, lower results were found in India (15.96%), Nepal (57.7%), United Arab Emirates (UAE) (58.6%), Pakistan (56.6%), Sri Lanka (35.5%), Kenya (27.7%), Ghana (76%), Sudan (49.8%), and African region systematic review (68%) (Abdin & Mohammed, 2021 ; Amponsah et al, 2022 ; Atal et al, 2021 ; Atif et al, 2016b ; Galappatthy et al, 2021b ; Nyabuti et al, 2020 ; Ofori-Asenso et al, 2016 ; Rabbani et al, 2023 ; Shrestha et al, 2021 ). These lower results could be attributed to the non-establishment or non-enforcement of the regulatory policies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 30 However, it is lower than studies conducted in Ethiopia (58.1%), 30 Italy (39.1%), 14 Nepal (48.46%), 15 Sierra Leone (94.9%) 31 and United Arab Emirates (43.8%). 32 The variation in results could be due to differences in study design, study setting and study population. Caution should be exercised when comparing results between the current study and studies conducted in Bangladesh, Ethiopia, Sierra Leone and the United Arab Emirates due to differences in the study population.…”
Section: Discussionmentioning
confidence: 99%